Analysis of the Formulation of Regional Regulation Number 4 of 2023 Concerning the Empowerment of Micro, Small and Medium Enterprises in Kepahiang Regency: Analisis Formulasi Peraturan Daerah Nomor 4 Tahun 2023 Tentang Pemberdayaan Usaha Mikro, Kecil Dan Menengah Di Kabupaten Kepahiang - Maryatun, Maryatun; Dani, Rahiman; Harmiati, Harmiati (JURNAL ISIP VOICE : Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This study aims to determine the Formulation of Regional Regulation Number 4 of 2023 concerning the Empowerment of Micro, Small and Medium Enterprises in Kepahiang Regency, using Budi Winarno's formulation theory that the preparation of Regional Regulations consists of 4 stages, namely; formulation of problems (Defining Problem), preparation of policy agendas, selection of alternative policies, and determination of policies. Data collection using interview, observation, and documentation techniques. Data analysis techniques using descriptive qualitative analysis. Based on the results of data analysis and findings obtained in the field, it can be concluded that, 1) issues or problems that are of serious concern to the local government, especially the Trade, Cooperatives and UMKM Service, the Kepahiang Regency DPRD and the MMS UMKM Association have been considered in the preparation of Kepahiang Regency Regional Regulation No. 4 of 2023 concerning the Empowerment of Micro, Small and Medium Enterprises. 2) Selection of alternative policies in the framework of the preparation of Kepahiang Regional Regulation No. 4 of 2023 to provide support and facilitation as well as regulations for MSMEs. Alternative policies that are very important and have a major impact on Micro, Small and Medium Enterprises (MSMEs) have been approved, consisting of; Empowerment of Micro, Small and Medium Enterprises, such as; growth of independence, togetherness and entrepreneurship of MSMEs, development of businesses based on regional potential, ensuring legal certainty in the implementation of empowerment and protection of MSMEs, criteria for micro, small and medium enterprises, in a separate chapter it is necessary to include the authority of the regional government, regarding licensing, protection of micro and small businesses, capital for micro, small and medium enterprises, 3) Determination of policies is the fourth stage in the formulation of the preparation of Kepahiang Regency Regional Regulation No. 4 of 2023 concerning the Empowerment of Micro, Small and Medium Enterprises, The policy taken is in the form of Kepahiang Regency Regional Regulation No. 4 of 2023 concerning the Empowerment of Micro, Small and Medium Enterprises, the Regional Regulation was stipulated on September 26, 2023, promulgated on September 26, 2023 and came into effect on September 26, 2023, source: Kepahiang Regency Regional Gazette 2023 Number 38 through the Kepahiang Regency DPRD meeting.